Structural characterization of iterative polyketide synthases - Tan, Jackie Yen (Nanyang Technological University, 2021)
Polyketide synthases are large multi-domain proteins found in bacterial and fungal species that synthesize structurally complex compounds called polyketides. Polyketides have strong antibacterial, antitumoral, and anticancer effect, and have therapeutic potential. Iterative polyketide synthases (iPKS) are one of the types of polyketide synthase and uses its domain iteratively to synthesize a polyketide chain product. While the individual domains in iPKSs are well studied, the full-length structures of iPKSs remain largely uncharacterized. As such, structural characterization of iPKS for the purpose of rational engineering and fine-tuning polyketide products remains an ongoing effort.